Marketing of Mexican cycads (Zamiaceae) in Atlixco, Puebla. An exploratory study - Mayett Moreno, Yésica; Salomé Castañeda, Edith; Barajas Domínguez, Ma. Isabel (Revista Mexicana de Ciencias Agrícolas, 2018)
Mexican cycads are long-lived plants with high ornamental potential consequently their wild populations have been extracted for marketing purposes. This extraction along with other pressures such as habitat destruction, have led to protection of wild populations by national and international laws, therefore in Mexico they are considered a priority for biological conservation. Its propagation in nurseries for commercial and reforestation purposes is recommended, and matches the need to conduct market research to provide information linking production-marketing under a sustainable dynamic. This is an exploratory, descriptive and cross-sectional study on Mexican cycads (Zamiaceae) marketing in Atlixco, Puebla. Overall 107 nurseries were visited from June 2012 to March 2013; 383 potential consumers of ornamental plants and 13cycadretailersweresurveyed.Cycadsaleswereidentified in 57% of these nurseries, and in 40.9% of them 4 Mexican species were on sale: Zamia Furfuraceae, Dioon edule, Dioon spinulosum and Ceratozamia sp., of which adult plants extracted from wild populations are traded. Differentiated marketing is recommended, according to actors involved in this chain, highlighting its ecological, cultural and economic relevance.
Keywords: sustainable agribusiness; ornamental purchase; threatened species